The Duxbury Sunken Forest-Constraints for Local, Late Holocene Environmental Changes Resulting from Marine Transgression, Duxbury Bay, Eastern Massachusetts, USA - Gontz, Allen M.; Maio, Christopher V.; Rueda, Laura (JOURNAL OF COASTAL RESEARCH, 2013)
The present marine transgression has forced geological and ecological zones vertically higher and landward since the late Pleistocene. A recent investigation in Duxbury Bay, Massachusetts, identified 18 Juniperus virginiana tree stumps emergent on an intertidal flat immediately seaward of a small marsh and pond situated between two eroding drumlins. The position of each stump was mapped with global positioning system (GPS), and its elevation with respect to mean lower low water was surveyed. Samples were selected from four stumps with elevations ranging from 2.03 and 0.75 m above mean lower low water for radiocarbon dating. The samples returned calibrated ages between 2219 +/- 94 and 2867 +/- 79 cal YBP, with the topographically highest sample returning the youngest date. Stump positions suggest a landscape gradient of 1.4 mm/yr between 2000 and 3000 cal YBP. The results are comparable with high-resolution studies of sea level in eastern Massachusetts for the same time period. Comparison of the youngest paleostumps with modern living trees suggests a dramatic change in the landscape gradient, an increase to 1.8 mm/yr. While this is contrary to sea-level studies nearby, it may represent an increase in the energetics of Duxbury Bay and resultant coastal erosion as the bay floods. The site can be used to put the impacts of changing sea-level rates into a landscape evolution framework.
Keywords: Cape Cod Bay; Coastal evolution; paleoforest; Radiocarbon dating; sea level; tree stumps